How are school dropouts related to household characteristics? Analysis of survey data from Bangladesh - Nusrat Farah; Mukti P. Upadhyay (Cogent Economics & Finance, 2017)
Human capital accumulation is one of the key drivers of economic growth especially in developing countries that are trying to catch up in per capita income with the developed world. A high dropout rate of children from school can significantly impede growth. This paper presents evidence on school dropout rate being affected by household characteristics and social background. We investigate dropouts by using a large data-set from the Bangladesh Demographic and Health Survey, 2011. A fractional logit model, a beta regression model, and for comparison a simple OLS model all indicate our empirical strategy to be fairly robust. The large incidence of households having a child quitting school to enter the labor market also allows us to study the dropout using a probit model. We find many interesting results. Children from poor families with less educated parents drop out sooner with a lasting effect on educational outcomes. Households that have more than three children or more than five members also experience greater quit rates. Richer and richest categories of households have the lowest dropouts. Those facing a costly commute to school or having no access to electricity also quit earlier. We also present evidence on several other factors with important policy implications. Our results suggest that any strategy that seeks to encourage human capital accumulation must simultaneously address the school dropout rate through a combination of such factors as promotion of female education and expansion of credit for small businesses.
Keywords: 330; school dropouts; demographic and household characteristics; fractional logit; beta regression; probit model; Bangladesh